Pengembangan Video Pembelajaran Berbantuan Videoscribe Pada Mata Pelajaran IPS Materi Kegiatan Ekonomi Kelas IV SD Negeri 7 Bakam - Merlina; Eka Rachma Kurniasi; Hevitria (JBES (Journal Basic Education Skills), 2023)
The lack of use of instructional media and the failure to integrate learning media materials into students' daily lives became the driving force for this research. The purpose of this study was to determine the validity and applicability of video scribe assisted learning films for economic activity content. Research and development (R&D) is the methodology used, and the ADDIE development model (analysis, design, development, implementation and evaluation) is used. By using quantitative and qualitative descriptive data, the collected data was analyzed. Interview sheets, test kits, and questionnaires or questionnaires are used as data collection procedures and tools. Grade IV students at SD Negeri 7 Bakam became research participants. This research produces learning video materials that are "very valid and practical" using videoscribe. This can be seen from the findings of 85% validation by linguists, 77.7% by media experts, and 95.7% by material experts. In addition, the results of the student response survey used to assess the usefulness of learning films in small and large courses were both 100%. With small classes having an average student score of 51.5% and large classes having an average student score of 90%, the creation of videoscribe-assisted learning videos is able to influence learning achievement results in terms of students' cognitive elements.